MK2–TNF–Signaling Comes Full Circle. Issue 3 (March 2018) - Menon, Manoj B.; Gaestel, Matthias
Abstract : MK2 (p38 MAPK -activated protein kinase 2) is essential for tumor necrosis factor (TNF) biosynthesis, mainly operating by post-transcriptional regulation. Deletion of the gene encoding MK2 strongly reduced serum TNF and protected against endotoxic shock, demonstrating the positive role of p38 MAPK /MK2 in TNF signaling at the level of ligand expression. Recent evidence indicates that MK2 directly phosphorylates the TNF receptor interactor RIPK1 and suppresses its activity, thereby limiting TNF-mediated apoptosis and necroptosis – pointing to a more complex, double-edged role of MK2 in TNF signaling. In addition, novel MK2 substrates have emerged in the DNA damage response, autophagy, and obesity, making MK2 a multifunctional kinase at the crossroads of stress response and cell death. We therefore propose a more general role of p38 MAPK /MK2 signaling in the timely coordinated onset and resolution of inflammation and beyond. Highlights: MK2 regulates biosynthesis of TNF and other cytokines at the post-transcriptional level by phosphorylating and inactivating the mRNA-destabilizing and translation-inhibiting protein tristetraprolin (TTP). Phosphorylation of the TNF receptor-interacting protein kinase RIPK1 by MK2 inhibits autophosphorylation of RIPK1 and its integration into cytoplasmic cytotoxic complexes, and thus suppresses TNF-dependent apoptosis and necroptosis. The p38/MK2 pathway negatively regulates SMAC mimetic (SM)-induced RIPK1 kinase-dependent TNF production in myeloid cells. Thus, p38/MK2 coinhibition emerges as a therapeutic strategy to circumvent SM resistance in leukemia, aiding in autocrine TNF-induced apoptosis. Novel roles for MK2 are emerging in cancer, inflammation, and autophagy with the identification of novel substrates, such as TRIM29, BECN1, and CEP131, and their distinct loss-of-function phenotypes.